Sexual dimorphisms in leukocyte trafficking in a mouse peritonitis model. Issue 5 (2nd July 2015) - Kay, Emma; Gomez‐Garcia, Lorena; Woodfin, Abigail; Scotland, Ramona S.; Whiteford, James R.
Abstract : Differences in inflammatory response between male and female C57BL6 mice. Abstract : Sexual dimorphisms exist in the incidence and severity of many diseases, with females demonstrating relative protection from inflammatory conditions. The extent and mechanisms by which excessive leukocyte recruitment underlies these differences are not well established, and better understanding is essential for the development of targeted therapies. Here, we set out to compare the male and female inflammatory response in a murine zymosan‐induced peritonitis model and to understand how leukocyte subsets are mobilized from storage pools in both sexes. This work shows that female C57BL/6 mice recruit fewer classical monocytes and neutrophils during zymosan‐induced peritonitis. In addition, sex differences were evident in the circulation, as female mice showed reduced neutrophilia and monocytosis vs. male counterparts, despite having similar mobilization from BM stores. Importantly, we show that storage and trafficking of splenic leukocytes during acute inflammation are distinct between the sexes. Male mice have greater splenic stores of neutrophils and classical and nonclassical monocytes, despite similar spleen sizes, signifying another source of potential pathogenic leukocytes. This work demonstrates that males and females have distinct leukocyte‐trafficking profiles in acute inflammation and suggests that the spleen, not the BM, plays a role in determining sex differences in the available pool of immune cells. Such dimorphisms demonstrate the importance of considering gender in assay development, drug design, and clinical trials.